Determinant Analysis of Bilateral Trade Between Indonesia and Yemen During the Period 1990-2015: A Gravity Model Approach - sabaruddin, sulthon sjahril (Universitas Airlangga, 2016)
This study examines the factors that influence the performance of bilateral trade between Indonesia and Yemen. In conducting the study, the authors use the conventional bilateral trade model is modified gravity model of international trade approach by using multiple regression analysis with Ordinary Least Square method. The analysis finds that the three independent variables that significantly affect the value of bilateral trade between Indonesia –Yemen is the GDP of Yemen, political uncertainty and security in Indonesia, as well as the presence of Indonesian Representative in the Republic of Yemen. While other independent variables namely Indonesia's GDP and political uncertainty and security in Yemen, based on the conclusions statistically, the two independent variables do not yet have enough evidence to say that the GDP of Indonesia and political uncertainty and security in Yemen significantly affect bilateral trade between Indonesia-Yemen. This trade gravity model previously passed testing assumptions multiple regression analysis with hypothesis testing and the accuracy of the model. Keywords: Economic Diplomacy, Bilateral Trade, Gravity Model, Multiple Regression Ordinary Least SquareJEL: F14, F15, F17